«Civilizadores del pueblo»: Maestros Primarios y Estado en Lima, 1860 - ca. 1905 - G. Antonio Espinoza (Caravelle)
With the establishment of municipal schools in the 1860s, Lima’s teachers gradually built a collective identity to improve their working conditions and to increase their prestige. Partially overcoming diverse training experiences, teachers strengthened their bonds, interacted with authorities, updated their knowledge, and represented themselves as specialists, through partnerships, periodicals, conferences, and other activities.